Streamlining the planning approval process for a sustainable urban development – a case study for unwinding manmade complexities - Ibrahim, Rahinah; Kweku, Hammah Norris (Hakim Sabzevari University, 2018)
The urban development process displays regressive tacit-dominant knowledge areas and their tacit level would impede their movements during multi-level knowledge transfers among stakeholders. The accuracy of a knowledge may be distorted when recipient stakeholders fail to understand a specific knowledge for its purpose. Earlier studies by the authors had highlighted complex yet dynamic environmental operating environment in most planning approval procedure. The paper presents a recent completed doctoral study which attempted to apply the Malaysian One-Stop Centre planning process for the city of Accra, Ghana. It centres on the Discontinuity in Organizations (D-I-O) theory which proposes “Knowledge” as the seventh Contingency Factor in managing knowledge flows in such operating condition. The theoretical foundation describes how four dynamic operating characteristics which—when combined and not well-mitigated—could lead towards organizational performance failures hence the projects’ socio-economic failures in providing adequate housing to the masses. There is a need for awareness and understanding of the multiple organizations involvement, the mixture of sequential and concurrent workflows, high interdependent tasks, and regressive nature of tacit knowledge throughout the different phases of an urban project’s lifecycle development process. The paper discusses the impacts on the organizations involved and how to mitigate them effectively to achieve an inclusive sustainable urban development. The paper presents the potential of streamlining the complex planning approval process which could improve management of a seemingly less understood tacit world of property development into a formidable sustainable urban development strategy.